Морфологические особенности органогенеза почек крыс развивавшихся под влиянием эналаприла и нифедипина - Акіншевич, І.Ю. (Таврический медико-биологический вестник, 2012)
Вивчений органогенез остаточних нирок ембріонів і плодів 112 самиць щурів породи «Вістар», отриманих в семи серіях експерименту, у віці з 15-х по 22-у добу нормальної вагітності і від самок, що
отримували терапевтичну, субтоксичну і токсичну дозу еналапріла і ніфедіпіна. Еналапріл змінює органогенез нирок і веде до їх різкого недорозвинення із зменшенням кількості нефронів і переважною
поразкою канальцевої системи. Прийом ніфедіпну призводить до незначного уповільнення розвитку нирок і деформації ниркових тілець. Найменш істотні морфологічні зміни присутні в остаточних нирках після прийому еналапріла в терапевтичній дозі, і найбільш істотні – після застосування субтоксичної дози. При прийомі ніфедипіну спостерігаються дозозалежні морфологічні зміни. Найбільш істотні вони
після прийому токсичної дози і найменші – після введення терапевтичної дози. Organogenesis of rat metanephros from 15th for the 22th days of gestation from 112 «Vistar» female
rats got in seven series of experiment were investigated. Control groop metanephros and from females, gettings the therapeutic, subtoxic and toxic dose of enalapril and nifedipin were studied. Enalapril changes metanephros organogenesis and conduces to their sharp excalation with diminishing of nephron number and
primary defeat of the tubular system. The nifedipin reception results in insignificant deceleration of metanephros development and deformation of renal corpuscles. The least substantial morphological changes are in metanephros after the reception of enalapril in a therapeutic dose, and most substantial – after application of subtoxic dose. At a nifedipin reception morphological changes depends from the dose. They are most substantial after the reception of toxic dose and the least – after introduction of therapeutic dose.